2010
DOI: 10.1007/s11661-009-0161-2
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Arm Spacing Affecting Mechanical Properties and Wear Behavior of Al-Sn and Al-Si Alloys Directionally Solidified under Unsteady-State Conditions

Abstract: Alloys of Al-Sn and Al-Si are widely used in tribological applications such as cylinder liners and journal bearings. Studies of the influence of the as-cast microstructures of these alloys on the final mechanical properties and wear resistance can be very useful for planning solidification conditions in order to permit a desired level of final properties to be achieved. The aim of the present study was to contribute to a better understanding about the relationship between the scale of the dendritic network and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 22 publications
2
33
0
10
Order By: Relevance
“…It is observed in Figures 6a and 6b that power laws equal to -1.1 and -0.55 characterize the experimental variation of primary spacing with growth rate and cooling rate, respectively, i.e, λ1 = 96(VL) -1.1 and λ1 = 396(TR) -0.55 . This is in agreement with observations reported by ROCHA et al [10], PERES et al [5], CARVALHO et al [7], CRUZ et al [15] BARROS et al [13] COSTA et al [12] and GOMES [16] that exponential relationships and λ1 = constant(VL) -1.1 and λ1 = constant(TR) -0.55 best generate the experimental variation of primary dendritic arms with VL and TR along the unsteady-state solidification of Al-Cu, Al-Si, Al-Sn, Al-Cu, Al-Cu-Si and Al-Cu-Si alloys, respectively. With a view to analyzing the effect of Si element in binary Al-3wt.% Cu alloy as well as the influence of growth direction on the length scale of the dendritic microstructure (1) the average, maximum and minimum values of the correlation between 1 and TR of this work are plotted in Figure 7 and compared with the experimental equations obtained by BARROS et al [13] and GOMES [16], whose works have been developed to horizontal and upward directional solidification, respectively.…”
Section: Resultssupporting
confidence: 93%
“…It is observed in Figures 6a and 6b that power laws equal to -1.1 and -0.55 characterize the experimental variation of primary spacing with growth rate and cooling rate, respectively, i.e, λ1 = 96(VL) -1.1 and λ1 = 396(TR) -0.55 . This is in agreement with observations reported by ROCHA et al [10], PERES et al [5], CARVALHO et al [7], CRUZ et al [15] BARROS et al [13] COSTA et al [12] and GOMES [16] that exponential relationships and λ1 = constant(VL) -1.1 and λ1 = constant(TR) -0.55 best generate the experimental variation of primary dendritic arms with VL and TR along the unsteady-state solidification of Al-Cu, Al-Si, Al-Sn, Al-Cu, Al-Cu-Si and Al-Cu-Si alloys, respectively. With a view to analyzing the effect of Si element in binary Al-3wt.% Cu alloy as well as the influence of growth direction on the length scale of the dendritic microstructure (1) the average, maximum and minimum values of the correlation between 1 and TR of this work are plotted in Figure 7 and compared with the experimental equations obtained by BARROS et al [13] and GOMES [16], whose works have been developed to horizontal and upward directional solidification, respectively.…”
Section: Resultssupporting
confidence: 93%
“…The mechanical properties of the A356 alloy, not only depend on the dendritic structures, but also on the sizes and morphologies of the eutectic Si particles [7,8]. The eutectic Si of untreated A356 presents a coarse plate-like structure, which will deteriorate the mechanical properties (especially the ductility) of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of directional solidification studies have been reported in the last decades to point out the effect of microstructure upon the mechanical properties, and different approaches and equations have been used with the purpose of modeling both theoretically and experimentally the primary and secondary dendrite arm spacings as a function of alloy solute concentration (C O ), transient metal-mold heat transfer coefficient (h i ), tip growth rate (V L ), temperature gradient (G L ) ahead of the macroscopic solidification front, tip cooling rate (T R ) in the melt, type of mold and melt superheat [14][15][16][17][18][19][20][21][22][23][24][25] . Most studies have shown that for steady or unsteady growth conditions, the primary dendrite arm spacings decrease as the solidification rate or temperature gradient increases; however, there is no agreement in the literature regarding the effect of the alloy solute content on primary spacings.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed, however, that these predictive theoretical models did not generate the experimental observations concerning the unsteady-state solidification of Al-Cu and Sn-Pb alloys 20 . The insertion of analytical expressions for V L and T R into experimental equations has been proposed in order to establish experimental formulae that relate cellular 19,22 and dendritic 20,23 spacings with the unsteady-state solidification variables. On the other hand, various numerical methods including cellular automata [26][27][28] , front-tracking methods [29][30][31] , phase field techniques [32][33][34] and level set methods [35][36] have been developed to study the growth of dendrites.…”
Section: Introductionmentioning
confidence: 99%